EFFECTIVENESS OF RANGE OF MOTION TO INCREASE JOINT MOTION RANGE IN STROKE PATIENTS - Aninda Maris Sustika; Arista Maisyaroh; Eko Prasetya Widianto; Laili Nur Azizah (UPT Penerbitan Universitas Jember, 2020)
Background: Stroke patients by 80% experience hemiparesis (partial paralysis on one side of the body). Muscle contractions are influenced by the body's motion system in stroke patients who experience weakness. Range of Motion is a muscle strength training given to increase muscle mass and muscle tone to increase the normal and complete perfection of joint motion. Most of the current research focuses on increasing muscle strength in stroke patients. Objectives: literature review aims to determine the effectiveness of Range of Motion there is an increase in muscle strength stroke patients. Method: In preparing the Literature review using the PRISMA checklist and PICOS in the selection determine the inclusion criteria. Secondary data obtained from reputable journals both national and international with a predetermined discussion. Results: The results of several articles on Range of Motion therapy to increase the range of joint motion in patients with stroke. Effective at least 2 times a day within 5-15 minutes for 8 days in 2 weeks can affect the increase in range of motion in the upper and lower extremity joints. Keywords: Range Of Motion, Stroke